A characterisation of trading equilibria in market games - Manipushpak Mitra; Indrajit Ray; Souvik Roy (Cardiff University, Cardiff Business School, 2020)
We provide a full characterisation of the set of trading equilibria (in which all goods are traded at a positive price) in a strategic market game (as introduced by Shapley and Shubik),for both the "buy and sell" and the "buy or sell" versions of this model under standard assumptions on the utility functions.We also interpret and illustrate our main equilibrium-characterising condition, using simple examples.
Keywords: C72; D44; 330; strategic market game; trading equilibrium; buy and sell; buy or sell